Captain James A. Baker of Houston, 1857-1941 - Kirkland, Kate Sayen, 1944- (Book collections on Project MUSE., 2012)
Captain James A. Baker, Houston lawyer, banker, and businessman, received an alarming telegram on September 23, 1900: his elderly millionaire client William Marsh Rice had died unexpectedly in New York City. Baker rushed to New York, where he unraveled a plot to murder Rice and plunder his estate. Working tirelessly with local authorities, Baker saved Rice's fortune from more than one hundred claimants; he championed the wishes of his deceased client and founded Rice Institute for the Advancement of Literature, Science and Art-today's internationally acclaimed Rice University. For fifty years Captain Baker nurtured Rice's dream. He partnered with leading lawyers to create Houston's first nationally recognized law firm: Baker, Botts, Lovett & Parker, now the worldwide legal practice of Baker Botts L.L.P. He chartered several Houston businesses and utility companies, developed two major regional banks, promoted real estate projects, and led an active civic life. To expand the Institute's endowment, Baker invested William Marsh Rice's fortune with local entrepreneurs, who were building homes, office towers, commercial enterprises, and institutions that transformed Houston from a small town in the nineteenth century to an international powerhouse in the twenty-first century. Author Kate Sayen Kirkland explored the archival records of Baker and his family and firm and carefully mined the archives of Baker's contemporaries. Published as part of Rice University's centennial celebration, Captain James A. Baker of Houston, 1857-1941 weaves together the history of Houston and the story of an influential man who labored all his life to make Houston a world-class city.